Late-stage optimization of a tercyclic class of S1P3-sparing, S1P1 receptor agonists. Issue 2 (15th January 2016) - Horan, Joshua C.; Kuzmich, Daniel; Liu, Pingrong; DiSalvo, Darren; Lord, John; Mao, Can; Hopkins, Tamara D.; Yu, Hui; Harcken, Christian; Betageri, Raj; Hill-Drzewi, Melissa; Patenaude, Lori; et al.
Graphical abstract: Abstract: Poor solubility and cationic amphiphilic drug-likeness were liabilities identified for a lead series of S1P3-sparing, S1P1 agonists originally developed from a high-throughput screening campaign. This work describes the subsequent optimization of these leads by balancing potency, selectivity, solubility and overall molecular charge. Focused SAR studies revealed favorable structural modifications that, when combined, produced compounds with overall balanced profiles. The low brain exposure observed in rat suggests that these compounds would be best suited for the potential treatment of peripheral autoimmune disorders.